A misdiagnosed myasthenia gravis with anti-muscle-specific tyrosine kinase antibodies with possible childhood onset - Nikolić, Ana V; Lavrnić, Dragana V; Basta, Ivana Z; Nikolić, Dimitrije M; Apostolski, Slobodan A (Vojnosanitetski pregled, 2015)
Introduction. Childhood onset myasthenia gravis associated with anti-muscle-specific tyrosine kinase antibodies is very rare and atypical in presentation. Case report. As a baby, the presented patient was choking and sleeping with open eyes. She had weak cry and breathing difficulties. In childhood, there were frequent falls and fluctuating swallowing difficulties. At the age of 19 she was misdiagnosed with Miller Fisher syndrome due to the presence of diplopia, ataxia and hyporeflexia with spontaneous recovery. Repetitive nerve stimulation test was normal. Four years later, after several relapses, there was significant decrement on facial muscles. Neostigmine test was negative, provoking muscle fasciculations. Serum anti-muscle-specific tyrosine kinase antibodies were positive. With cyclosporine therapy she achieved the minimal manifestations status. Conclusion. The presented case confirms that childhood onset myasthenia gravis associated with anti-muscle-specific tyrosine kinase antibodies is often with atypical presentation and spontaneous remissions, so it could be easily misdiagnosed.